2020
DOI: 10.1111/1365-2664.13719
|View full text |Cite
|
Sign up to set email alerts
|

Multi‐species restoration accelerates recovery of extinguished oyster reefs

Abstract: A multi‐species approach to habitat restoration may boost the key processes (e.g. recruitment) that enable foundation species to overcome barriers to recovery. Natural systems tend to be formed by co‐occurring foundation species whose synergy drives ecological productivity and resilience beyond that of single foundation species. Yet, restoration remains primarily a single‐species focus enterprise where positive interactions are seldom incorporated into planning. A multi‐species approach that prioritizes specie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 83 publications
1
30
0
Order By: Relevance
“…By increasing larval settlement, restorers also have the capacity to reduce the risk of poor settlement during low recruitment periods; spatial and temporal variability of recruitment being notoriously variable in marine systems. Moreover, restoration may be accelerated if sound technology is used in tandem with times of natural peak recruitment and the provision of competitor‐free substratum (Lipcius et al, 2021; McAfee et al, 2021). By putting sound back into currents, these gradients of larval transport (sensu Garth, 1966) may become more navigable, such that they represent gradients of sound to aid restoration.…”
Section: Discussionmentioning
confidence: 99%
“…By increasing larval settlement, restorers also have the capacity to reduce the risk of poor settlement during low recruitment periods; spatial and temporal variability of recruitment being notoriously variable in marine systems. Moreover, restoration may be accelerated if sound technology is used in tandem with times of natural peak recruitment and the provision of competitor‐free substratum (Lipcius et al, 2021; McAfee et al, 2021). By putting sound back into currents, these gradients of larval transport (sensu Garth, 1966) may become more navigable, such that they represent gradients of sound to aid restoration.…”
Section: Discussionmentioning
confidence: 99%
“…For example, synchronizing soundscape enrichment with the timing of recruitment or interventions to provide competitor‐free substratum (McAfee and Connell 2020, McAfee et al. 2021) may increase the success of restoration initiatives.…”
Section: From Soundscapes To Muted‐scapesmentioning
confidence: 99%
“…First, we recorded soundscapes associated with three distinct marine habitats of southern Australia (Gulf St. Vincent, South Australia): a temperate rocky reef ecosystem, a sedimentary barren where oyster reefs historically existed but were lost to dredge fishing (Alleway and Connell 2015), and a large restoration site (20 ha) on which lost oyster reefs are being restored (McAfee et al. 2021; Appendix : Section S1). Based on sound pressure level and snapping shrimp snap counts, we found that acoustic characteristics increased from degraded to healthier habitats; the sedimentary habitat was the quietest, the rocky restoration site louder and natural rocky reef the loudest and contained the most snapping shrimp snaps (Appendix : Figs.…”
Section: From Soundscapes To Muted‐scapesmentioning
confidence: 99%
See 2 more Smart Citations